2014
DOI: 10.1158/1535-7163.mct-14-0487-t
|View full text |Cite
|
Sign up to set email alerts
|

An Antimesothelin-Monomethyl Auristatin E Conjugate with Potent Antitumor Activity in Ovarian, Pancreatic, and Mesothelioma Models

Abstract: Mesothelin (MSLN) is an attractive target for antibody-drug conjugate therapy because it is highly expressed in various epithelial cancers, with normal expression limited to nondividing mesothelia. We generated novel antimesothelin antibodies and conjugated an internalizing one (7D9) to the microtubuledisrupting drugs monomethyl auristatin E (MMAE) and MMAF, finding the most effective to be MMAE with a lysosomal protease-cleavable valine-citrulline linker. The humanized (h7D9.v3) version, aMSLN-MMAE, specifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Among the evaluable tumors for pancreatic cancer, the distribution of mesothelin membranous IHC staining scores was 0 (17%), 1þ (7%), 2þ (67%), and 3þ (10%); and for ovarian tumors, 0 (4%), 2þ (28%), and 3 þ (68%). Although the mesothelin staining frequency is consistent with prior published results (3)(4)(5)(6)16), some bias for higher frequency of expression may exist due to selection of IHC 3þ patients in the expansion cohorts. Representative images of IHC staining in both pancreatic and ovarian tumor specimens are shown in Fig.…”
Section: Biomarker Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Among the evaluable tumors for pancreatic cancer, the distribution of mesothelin membranous IHC staining scores was 0 (17%), 1þ (7%), 2þ (67%), and 3þ (10%); and for ovarian tumors, 0 (4%), 2þ (28%), and 3 þ (68%). Although the mesothelin staining frequency is consistent with prior published results (3)(4)(5)(6)16), some bias for higher frequency of expression may exist due to selection of IHC 3þ patients in the expansion cohorts. Representative images of IHC staining in both pancreatic and ovarian tumor specimens are shown in Fig.…”
Section: Biomarker Analysissupporting
confidence: 89%
“…Potential reasons for this include the inherent variability of assessing small cohorts, the inaccessibility of the ADC to tumor cells due to its relative hypovascular nature, as a result of the dense stromal structure of pancreatic lesions (32). In addition, mesothelin expression in pancreatic cancer may be heterogeneous, inaccessible (i.e., apical) or lost (3,16). Finally, primary resistance to chemotherapy in pancreatic cancer may be more prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using antibody-drug conjugate technology, the humanized mouse anti-mesothelin antibody 7D9 was linked to monomethyl auristatin E via a lysosomal protease-cleavable valine-citrulline dipeptide linker, and has demonstrated promising activity in preclinical models (152). A phase Ia/ II study of a mesothelin-directed antibody drug conjugate with an undisclosed cytotoxic drug (BMS-986148) was initiated in patients with advanced solid tumors, including mesothelioma, and this study is currently recruiting patients for enrollment (clinicaltrials.gov NCT02341625).…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…29 According to the previous studies, therapeutic antibodies conjugated with MMAE showed high antitumor efficiency in patients with hematologic malignancies and solid tumors. [30][31][32][33][34][35][36] We utilized a humanized anti-HER2 antibody, hertuzumab, conjugated with MMAE via a cleavable linker to generate hertuzumab-MC-Val-Cit-PAB-MMAE (hertuzumabvcMMAE for short). Our previous study has proven this ADC agent has a potent antitumor activity in HER2 positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%